Indirect ocean capture of atmospheric CO2: Part I. Prototype of a negative emissions technology. (March 2018) - de Lannoy, Charles-Francois; Eisaman, Matthew D.; Jose, Arun; Karnitz, Stephen D.; DeVaul, Richard W.; Hannun, Kathy; Rivest, Jessy L.B.
Highlights: Indirect ocean capture, a negative emissions technology, is experimentally tested. The electrochemical process removes CO2 from air by shifting the pH of seawater. Acid/base for the process is made via bipolar membrane electrodialysis (BPMED). Electricity consumed by BPMED dominates the energy cost of the process. Efficient BPMED at high acid/base concentration would greatly reduce energy cost. Abstract: We present the design, construction, characterization, and analysis of a prototype process for a novel electrochemical platform of candidate negative emissions technologies (NETs), termed indirect ocean capture. The IOC technologies remove carbon dioxide gas from the atmosphere by leveraging both air-ocean gas exchange and the pH sensitivity of the ocean's carbonate buffer system. The system characterized in this paper enables two configurations that capture CO2 either as a pure gas or as a solid mineral. Both configurations use the acid and base produced by the membrane electrodialysis of ocean water. The first configuration, termed the 'acid process', acidifies ocean water or brine to shift the carbonate buffer system towards dissolved CO2 gas, which is vacuum stripped from the acidified brine. The second configuration, termed the 'base process', adds base to the brine to shift the carbonate buffer system towards carbonate ions, which precipitates as CaCO3 . A closed loop cycle is achieved by returning this decarbonized and alkalinized brine to the ocean for additional CO2 absorption from the air. Our evaluation of this prototype scale system focused on the parameters that have the most influence on the ultimate cost of the extracted CO2 . In a concurrent techno-economic study, the most cost-sensitive parameters were shown to be the efficiencies of the anion and cation exchange membranes, the number and orientation of CO2 extraction membranes, and the volume of base required for CaCO3 precipitation. The measured parameters provide target values for commercial deployment. The experiments in this study were used to inform the concurrent techno-economic study that quantifies in detail the projected cost of avoided CO2 achievable with this process.